2007
DOI: 10.1007/s11095-007-9272-x
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Effects of Glycyl-Glutamate and Glycyl-Sarcosine on Gabapentin Oral Absorption in Rat

Abstract: These findings are unique in demonstrating that under physiologic, in vivo conditions, the luminal presence of glycyl-glutamate could dramatically enhance the Cmax and AUC(0-6 h) of gabapentin. The results are consistent with previous in situ intestinal perfusion studies in rat, and establish a functional interaction between the activities of PEPT1 and amino acid exchangers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Furthermore it was shown that an increase in gene expression was also possible with a standard diet by supplementation of a single dipeptide (Gly-Phe) [81]. In this case uptake of Gly-Sar and peptidomimetics via PEPT1 was increased as well [81,82].…”
Section: Amino Acids and Peptidesmentioning
confidence: 94%
“…Furthermore it was shown that an increase in gene expression was also possible with a standard diet by supplementation of a single dipeptide (Gly-Phe) [81]. In this case uptake of Gly-Sar and peptidomimetics via PEPT1 was increased as well [81,82].…”
Section: Amino Acids and Peptidesmentioning
confidence: 94%